Foliar K application to rainfed wheat in a soil testing high K as an option to improve K use efficiency, grain yield and yield components. (8th May 2020) - Limon-Ortega, Agustin; Munguia-Lopez, Juan P.; Espitia-Rangel, Eduardo
Abstract: Granular application of potassium (K) in soils testing high is generally not recommended. However, the effect of foliar K on rainfed wheat ( Triticum aestivum L.) under these soil conditions is largely unknown. The objective of this work was to identify the effect of K fertilizer on K use efficiency (KUE), grain yield and yield components of wheat. The data were collected until 2017 in an ongoing trial established in 2007 with eight treatments; two granular K rates (0 and 50 kg K ha −1 ); two foliar N rates (0 and 3 kg N ha −1 ); and two foliar K rates (0 and 3 kg K ha −1 ) in a split-split plot arrangement. Treatments were applied to the same plots each season. Treatment with foliar K resulted in the highest KUE response but the effect size varied according to the accumulated precipitation during the reproductive stage. On average, KUE was enhanced in crop seasons with water constrains (<179 mm) during the growth period but the converse was true as the amount of precipitation increased. In contrast, granular K had no effect on KUE irrespective of precipitation conditions. Application of foliar K increased grain yield as compared to granular K from 2988 to 3089 kg ha −1 . This enhancement was attributed to an increased number of grains per head. Therefore, foliar K application to wheat is suitable in a soil testing high K to enhance KUE and grain yield, overall in crop seasons with water constrains.